Probabilistic Sampling in Media and Communication Studies: Concept, Procedures, and Applications - Brahim DJENNAD; Mokhtar DJELLOULI (Eon)
This study aims to highlight the vital role of sample selection in media and communication research, as it serves as a fundamental tool for saving time, effort, and resources in data collection and analysis. The study's main goal is to clarify the concepts of the research population and sampling. It does this by carefully analyzing several types of probability samples, including stratified random sampling, systematic random sampling, and basic random sampling. It also addresses the procedures and practical applications associated with each type, providing illustrative examples from media and communication research. The findings reveal that the use of probability sampling significantly contributes to making certain that the research population is accurately represented, which will increase the dependability of the findings. Simple random sampling, for example, is found to be the most straightforward to use and provides equal chances for every component of the population, which makes it a suitable option when the population is comparatively homogeneous. However, by using specified intervals between items, systematic random sampling shows that it can structure the selection process and provide greater sample coverage. Conversely, stratified random sampling proves highly effective in studies requiring consideration of diversity and significant differences within a heterogeneous population.